Lower serum magnesium concentration and higher 24-h urinary magnesium excretion despite higher dietary magnesium intake in athletes: a systematic review and meta-analysis - Haixin Zhang; Ruwen Wang; Shanshan Guo; Qianqian Tian; Shuang Zhang; Liang Guo; Tiemin Liu; Ru Wang (Food Science and Human Wellness)
Magnesium plays a critical role in the human's life activities and energy metabolism. This study aimed to evaluate the magnesium status of athletes via a systematic review of cross-sectional studies. A comprehensive systematic search was conducted in PubMed, Web of Science, SPORTDiscus, Cochrane Library electronic databases, and other sources before April 5, 2021. Fourteen studies were included in the systematic review, involving 855 athletes and 521 control subjects. Serum magnesium concentration was significantly lower in athletes (mean difference (MD): −0.04 mmol/L; 95 % confidence interval (CI): −0.06 to −0.01; P = 0.02) in spite of significantly higher dietary magnesium intake (MD: 51.72 mg/day; 95 % CI: 14.62 to 88.83; P = 0.006). Meta-analysis showed that 24-h urinary magnesium excretion in athletes was significantly higher than that in the untrained population (MD: 0.76 mmol/day; 95 % CI: 0.11 to 1.41; P = 0.02). Despite higher total dietary magnesium intake, athletes generally have lower serum magnesium concentration and higher 24-h urinary magnesium excretion, demonstrating that the magnesium requirement of athletes is higher than the untrained population. It is necessary to carry out a dietary assessment and nutrition counseling to help athletes adopt proper diets to meet their nutritional needs in exercise.